Efektivitas Metode Demonstrasi Dalam Meningkatkan Keterampilan Membuat Terarium Bagi Anak Tunarungu - Ridho Pratama; Kasiyati Kasiyati (Universitas Negeri Padang, 2018)
This research was motivated by the problems found in SLBN 1 Padang Panjang there are five deaf students of class XI with monotonous teaching means them don’t understand the lesson and unawareness to make terarium according to the steps of manufacture, the purpose of this study was to check wether it is effective using demonstration methods to teach deaf students to make terarium in SLBN 1 Padang Panjang, research method that is pre-eksperimental kind of one group pretest - posttest design. Ratings in this study using the test instrument deed to calculate a child's ability to make terarium and tested in accordance with Mann Whitney test.The result esxplaned that effective demonstration methods to improve skills of making terrariums for deaf childrenn of class XI SLBN 1 Padang Panjang.this is evident from hypothesis testing Ha accepted by Uhit = 27 > Utab = 1.